2023
DOI: 10.1111/iju.15299
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights on the clinical, pathological, and molecular features of intraductal carcinoma of the prostate

Yushi Naito,
Masashi Kato,
Jun Nagayama
et al.

Abstract: Intraductal carcinoma of the prostate, a unique histopathologic entity that is often observed (especially in advanced prostate cancer), is characterized by the proliferation of malignant cells within normal acini or ducts surrounded by a basement membrane. Intraductal carcinoma of the prostate is almost invariably associated with an adjacent high‐grade carcinoma and is occasionally observed as an isolated subtype. Intraductal carcinoma of the prostate has been demonstrated to be an independent poor prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…In a limited case series, Ikeda et al observed the components of IDCP in nine patients with NEPC for whom tissue specimens were available at diagnosis [33]. Thus, the identification of IDCP may serve as a potential predictor of NEPC development; however, the association between IDCP and NEPC remains unclear and warrants further investigation [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a limited case series, Ikeda et al observed the components of IDCP in nine patients with NEPC for whom tissue specimens were available at diagnosis [33]. Thus, the identification of IDCP may serve as a potential predictor of NEPC development; however, the association between IDCP and NEPC remains unclear and warrants further investigation [34].…”
Section: Discussionmentioning
confidence: 99%